PERBANDINGAN DINDING PRECAST DAN BATA RINGAN TERHADAP BIAYA DAN WAKTU PADA FACADE PROYEK SUNCITY APARTMENT SIDOARJO - nur hanifah eka putri; I Nyoman Dita Pahang Putra; Anna Rumintang Nauli (Universitas Teuku Umar, 2021)
The choice of material type has a big influence in the aspect of workmanship which includes the amount of cost and time spent processing. One of the projects that requires selecting the type of material is the facade wall work. In general, wall materials use conventional materials such as lightweight bricks, along with technological advances, they begin to switch to other materials that support the cost and time, namely using precast or precast materials. Before materials that exist, namely precast wall and light brick wall, the differences in the existing materials and manufacture cause different stages of work which affect the implementation time and costs between precast wall and light brick work. This study uses data in the form of implementation images, RAB, HSPK, SNI 6897: 2008, and SNI 2837: 2008 to become the base of calculating costs and time of the two implementation methods. Then, analyze the two implementation methods to find out what causes differences in cost and implementation time requirements. Comparative analysis between the two methods of implementation shows that work with precast material costs Rp. 5,633,609,447 and the work time is 113.86 days, while work with light brick material requires a cost of Rp. 3,136,802,766 with an implementation time of 154 days. This shows that precast wall work is 44.32% more expensive than the light brick, but precast wall work can minimize the time by 26.1%.